Copper modified waste fly ash as a promising catalyst for glycerol hydrogenolysis - Rode, C. V.; Mane, R. B.; Potdar, A. S.; Patil, P. B.; Niphadkar, P. S.; Joshi, P. N. (Catalysis Today, 2012)
Several catalyst formulations using waste fly ash along with Cu were prepared and characterised by XRD, BET and TEM. These catalysts were also evaluated for the first time for hydrogenolysis of glycerol to 1,2 propanediol (1,2-PDO) in a batch reactor under 52 bar H-2 pressure in the temperature range of 473-513 K conditions. The fly ash pretreated by alkali using the fusion method and impregnated with Cu showed higher activity and stability for glycerol hydrogenolysis. Due to pretreatment with alkali at high temperature, transformation of alpha-quartz to the tridymite phase of SiO2 occurred. More importantly, use of alkali either during the pretreatment or the Cu loading step resulted in a high dispersion on the surface which was responsible for higher glycerol conversion and 1,2-PDO selectivity. The effects of temperature, Cu loading and solvent on glycerol conversion and product selectivities were also studied in this work. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: 1; 2-Propanediol; Alkali fusion; Cu loading; Fly ash; Glycerol hydrogenolysis